Infección latente por mycobacterium tuberculosis en estudiantes de medicina expuestos a un medio hospitalario - Guarniz Medina, Frank Jhonatan (2019)
Objective: To determine if exposure to a hospital environment is a risk factor for latent infection by Mycobacterium tuberculosis in medical students. Material and Method: A descriptive, comparative, cross-sectional study was carried out. PPD were applied to 98 UNT medical students among those not exposed and exposed to the hospital environment. For the statistical analysis, the Chi square test (X2) was used. Results: Of 98 students. We found a low prevalence of 5.1% of PPD positive in students not exposed to TB patients and a high prevalence of 20.4% of positive PPD in students exposed to TB patients; with a highly significant difference when buying both groups (p <0.01). The length of induration varies between 0 - 13 mm among all participants, with 5 and 10 mm cut-off points. Conclusions: There is a highly significant difference between Latent TB prevalence in medical students not exposed to TB patients versus students exposed to TB patients, being higher in the group of exposed students.